Canadian Coastal Seas and Great Lakes Sea Surface Temperature Climatology and Recent Trends. Issue 3 (3rd May 2016) - Larouche, Pierre; Galbraith, Peter S.
Abstract : Abstract. 28 years of satellite data were used to calculate sea surface temperature (SST) climatologies covering Canada's 3 surrounding oceans and the Great Lakes. Results show the imprint of major circulation features on the spatial distribution of the SST. Together with the Gulf Stream, the Labrador Current generates a strong spatial variability of SST on the east coast. Most of the Canadian Arctic, with the exception of Hudson Bay and the coastal Beaufort Sea region, is characterized by very small seasonal SST amplitude. Lake Erie is the water body having the largest seasonal SST amplitude, but for the oceanic regions, it is the southern Gulf of St. Lawrence and the adjacent Scotian Shelf. A trend analysis showed that many regions are undergoing rapid warming of the sea surface. However, warming is not spatially uniform. The strongest warming was detected in Baffin Bay and appears to result from the decreasing ice cover. Lake Superior is also showing a strong warming trend. These results have important implications for fisheries management because SST affects many species. Regions with small yearly amplitudes and warming trends might act as future cool water oases for some species.